Rotating string solutions: AdS/CFT duality in non-supersymmetric sectors - FROLOV, SERGEY (Elsevier, 2003)
We find the minimal energy solution describing a folded closed string located at the center of AdS5 and rotating simultaneously in two planes in S5 with two arbitrary SO(6) angular momenta J1 and J2. In the case when J1 = J2 = J? we observe the precise agreement between the leading coefficient in the large J? expansion of the energy of this solution and the minimal eigen-value of the 1-loop anomalous dimension matrix of the corresponding [J?, 0, J?] SYM operators obtained by Beisert, Minahan, Staudacher and Zarembo in hep-th/0306139. We find also perfect agreement between string and SYM results in cases of states with unequal spins dual to [J2, J1 ? J2, J2] operators. This represents a remarkable quantitative test of the AdS/CFT duality in a non-supersymmetric (and non-near-BPS) sector.
PUBLISHED
Keywords: Mathematics; String theory